Nuclear and cellular volumetric alterations in oral lichen planus and lichenoid lesions: a histomorphometric study - Khoo, S.P.; Primasari, A.; Saub, R. (2001)
There is presently no line of distinction between oral lichen planus and other oral lichenoid lesions. The aim of this study is to determine using histomorphometry, the differences between these lesions. Paraffin sections from 7 normal buccal epithelium, 19 oral lichen planus (LP), 14 oral lichenoid lesions (LL) and 7 discoid lupus erythematosus-like lesions (DLE-ll) were selected. The nuclear volume (V(N)) and cellular-volume (V(CELL)) of the epithelium were assessed using an image analyser. The V(N) and V(CELL), derived for both basal and spinal strata in LP and DLE-ll were 2.3 times more than that of normal tissues. There was a significant difference between LP and LL (P < 0.005) and between LL and DLE-ll (P < 0.001), but not between LP and DLE-ll. In conclusion, there appears to be a difference between LP, LL and DLE-ll and V(N) and V(CELL) may serve as potential discriminators between these groups of lesions.